PYLORIC STENOSIS CAUSED BY INGESTION OF CORROSIVE AGENTS : A CASE REPORT - yoely ardiansyah (HUMAN CARE JOURNAL, 2021)
Corrosive or caustic is a group of chemical which has the capacity to cause tissue injury on contact by a chemical reaction.Ingestion of a substance that causes a chemical reaction with mucosal tissue and  injures the  gastrointestinal and respiratory tract is caustic ingestion. Accidental ingestion of caustic agents may cause devastating injury in children. Eighty percent of corrosive poisoning occurs in children below five years. Children are particularly susceptible to the accidental exposure to such substances due to inadequate parental supervision and careless storing of these chemicals at homes. Pyloric stenosis or gastric outlet obstruction  is a well-known complication of caustic acid ingestion. The stenosis mostly occurs at the pylorus and antrum due to the pooling of the corrosive agent and the reflex pyloric spasm of the stomach after the ingestion. Typically corrosive acid ingestion leads to local reaction, oesophageal damage and gastric injury in that order. Isolated injury to the stomach resulting in pyloric stenosis is very rare, accounting to as little as 3,8% of all the cases of corrosive ingestion as reported in literature. A proper management including surgery is needed in this case to treat a child with pyloric stenosis caused by ingestion of corrosive agents. Keyword : Pyloric stenosis, accidental ingestion,  corrosive agents.